Experimental and computational studies of naphthyridine derivatives as corrosion inhibitor for N80 steel in 15% hydrochloric acid - Ansari K.R.; Quraishi M.A. (My University, 2025)
The inhibition effect of three naphthyridine derivatives namely 2-amino-4-(4-methoxyphenyl)-1,8-naphthyridine-3-carbonitrile (ANC-1), 2-amino-4-(4-methylphenyl)-1,8-naphthyridine-3-carbonitrile (ANC-2) and 2-amino-4-(3-nitrophenyl)-1,8-naphthyridine-3-carbonitrile (ANC-3) as corrosion inhibitors for N80 steel in 15% HCl by using gravimetric, electrochemical techniques (EIS and potentiodynamic polarization), SEM, EDX and quantum chemical calculation. The order of inhibition efficiency is ANC-1>ANC-2>ANC-3. Potentiodynamic polarization reveals that these inhibitors are mixed type with predominant cathodic control. Studied inhibitors obey the Langmuir adsorption isotherm. The quantum calculation is in good agreement with experimental results. © 2015 Elsevier B.V.